Pengaruh Kualitas Layanan, Kualitas Produk Dan Persepsi Harga Terhadap Keputusan Pembelian Botol Parfum Kosong Di Baracca Parfum Store - Virdiana Diva Zurinda; Fausta Ari Barata (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Perfume business prospects continue to show encouraging growth amidst increasingly fierce competition in the beauty and lifestyle industry. During the pandemic, perfume sales continue to increase, and there is even an increasing trend of online purchases. The price of perfume production can be considered quite cheap, especially if you have a trusted raw material supplier. Of course, by paying attention to quality and flexibility in the number of purchases, Baracca Parfum Store is present by providing solutions through empty perfume bottle products at competitive prices. This type of research uses quantitative research with Non-Probability Sampling with Purposive Sampling Technique. The population in this study were 100 respondents of Baracca Parfum Store consumers obtained from filling out questionnaires via google form with Likert scale calculations. The results of this study indicate that Service Quality (X1) has a positive and significant effect on Purchasing Decisions (Y), Product Quality (X2) has a positive and significant effect on Purchasing Decisions (Y), Price Perception (X3) has a positive and significant effect on Purchasing Decisions (Y), Service Quality, Product Quality and Price Perception simultaneously have a positive and significant effect on Purchasing Decisions (Y).